2022
DOI: 10.3390/plants11030304
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Transformation of Quercus ilex Somatic Embryos with a Gnk2-like Protein That Reveals a Putative Anti-Oomycete Action

Abstract: Holm oak is a key tree species in Mediterranean ecosystems, whose populations have been increasingly threatened by oak decline syndrome, a disease caused by the combined action of Phytophthora cinnamomi and abiotic stresses. The aim of the present study was to produce holm oak plants that overexpress the Ginkbilobin-2 homologous domain gene (Cast_Gnk2-like) that it is known to possess antifungal properties. Proembryogenic masses (PEMs) isolated from four embryogenic lines (Q8, E2, Q10-16 and E00) were used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…These previous studies of our group focused on the resistance of chestnut and its response to the Oomycete, indicating that C. crenata Ginkgobilobin-2-like gene and the encoded protein (Cast_Gnk2-like) might be important in chestnut resistance. In an in vitro tolerance assay with the pathogen P. cinnamomi, Serrazina, et al (2022) [20], observed that transgenic plants of holm oak (Quercus ilex) with the Cast_Gnk2-like were able to survive longer than non-transgenic ones [20]. Similar results were obtained in resistance tests against F. oxysporum in transgenic cucumber (Cucumis sativus) plants, which showed that the expression of Gnk2-1 conferred antifungal activity against the disease [25].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These previous studies of our group focused on the resistance of chestnut and its response to the Oomycete, indicating that C. crenata Ginkgobilobin-2-like gene and the encoded protein (Cast_Gnk2-like) might be important in chestnut resistance. In an in vitro tolerance assay with the pathogen P. cinnamomi, Serrazina, et al (2022) [20], observed that transgenic plants of holm oak (Quercus ilex) with the Cast_Gnk2-like were able to survive longer than non-transgenic ones [20]. Similar results were obtained in resistance tests against F. oxysporum in transgenic cucumber (Cucumis sativus) plants, which showed that the expression of Gnk2-1 conferred antifungal activity against the disease [25].…”
Section: Discussionmentioning
confidence: 84%
“…This work is part of the ongoing research program that aims to find solutions to the health problem regarding European chestnuts (C. sativa) and the pathogen P. cinnamomi [1]. This program involves an integrated approach using genomics, phenomics (precision phenotyping), transcriptomics, association mapping of traits, and histopathology, to reveal the mechanisms of the resistance of Asian species to infection by P. cinnamomi, and to transfer the knowledge for the improvement of resistance of European chestnut [7,9,13,[18][19][20][21][22]. The program is supported by a breeding program initiated in 2006, based on controlled crosses, from which segregated hybrid populations were obtained with the selection of new genotypes with improved resistance to P. cinnamomi, which soon will be disclosed to the market to be used as rootstocks.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Cano et al [304] demonstrated the successful transformation and regeneration of Holm oak (Q. ilex) with the same CsTL1 gene from chestnuts. More recently, Serrazina et al [305] demonstrated the successful A. tumefacians-mediated transformation of Q. ilex with the Ginkbilobin-2 homologous domain gene (Cast_Gnk2-like), which had previously been shown to exhibit antifungal activity [306]. The in vitro analysis of the transgenic plants demonstrated some resistance to the P. cinnamomi as judged by increased time post-inoculation to plant death of transgenic plants when compared to controls.…”
Section: Transgenic Oaksmentioning
confidence: 99%
“…This applies to holm oak, in which although somatic embryogenesis has been induced in zygotic embryos ( Mauri and Manzanera, 2003 ), flower tissues ( Blasco et al., 2013 ; Barra-Jimenez et al., 2014 ) and leaf and apex explants derived from in vitro cultures ( Martinez et al., 2017 ; 2020 ; 2021 ), the induction frequency is usually low and the success of the technique is highly genotype dependent. Procedures for Agrobacterium -mediated genetic transformation in holm oak have been reported, but the transformation rates are low (less than 2.5%) and long in vitro culture periods are required to get regeneration ( Cano et al., 2020 ; Serrazina et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%